Determinants of Sharia Accounting Students’ Competence in Facing Industry 5.0 at State Islamic Religious Colleges in Java Island - Wardiyah, Mia Lasmi; Dzikrayah, Fithri; Ponirah, Ade (Journal of Islamic Economics and Business, 2026)
The advent of Industry 5.0 has intensified the demand for graduates to possess not only technical skills but also adaptive, innovative, and ethical competencies. In the context of State Islamic Religious Colleges (PTKIN) in Java, the readiness of Sharia accounting students to meet these demands remains uncertain, particularly regarding the integration of technology and Islamic values. This study examines the determinants of Sharia accounting students’ competence using the Theory of Planned Behavior framework, incorporating factors related to the learning process and educational environment. Data were collected through a questionnaire survey of Sharia accounting students from superior-accredited PTKIN in Java and analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that enriching educational experiences and the learning environment significantly influence student competence, while academic challenges, active learning, and staff–student interaction do not show significant effects. These results suggest that PTKIN should strengthen curriculum relevance by integrating technology, big data, and artificial intelligence into Sharia accounting education, while encouraging students to proactively develop Industry 5.0–related technological competencies.